Pengembangan Lembar Kerja Peserta Didik Matematika Berbasis Contextual Teaching and Learning - Pratiwi Nurussalamah; Elya Rosalina; Eka Lokaria (Journal of Elementary School (JOES), 2023)
This study aims to develop Contextual Teaching and Learning (CTL)-based mathematics Student Worksheets for Grade IV students at SD Negeri 34 Lubuklinggau which are valid and practical to be used in learning. The sample of fourth grade students at SD Negeri 34 Lubuklinggau consisted of 6 small group test students. This type of research researchers uses the development of Research and Development (R&D). The data collection technique used a validation questionnaire for linguists, material experts, media experts and a practicality questionnaire for teachers and students. Based on the results of the analysis by the three experts, the scores obtained by linguists were 0.81, material experts were 0.82 and media experts were 0.82, the overall average was 0.82 with a very valid category. While the results of the analysis of the practicality sheets of teachers and students obtained scores of 95% and 92.8% with an overall average of 93.9% in the very practical category. So that the Mathematical Student Worksheet based on Contextual Teaching and Learning (CTL) meets valid and practical criteria. Keywords: Development, Worksheets, Mathematics, CTL